2014
DOI: 10.1007/s00403-014-1455-9
|View full text |Cite
|
Sign up to set email alerts
|

In psoriasis, levels of hope and quality of life are linked

Abstract: Psychological resources such as hope have been suggested to positively influence quality of life (QoL) in chronic disorders. Here, we determined hope levels of psoriasis vulgaris in-patients and analyzed their relation to QoL. A total of 60 (29 male) patients were assessed for their QoL with a generic tool (WHOQOL-BREF) and a skin disease-specific instrument, the Dermatology Life Quality Index (DLQI). Hope levels were determined by use of the Basic Hope Inventory. We found a positive correlation between hope a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Other benefit findings were reported in the studies of Johnson et al (2001), showing that social support for HIV-positive people is inversely related to depressive symptoms and a lack of hope; Waynor et al (2012), demonstrating that hope and symptoms are inversely related; Hawro et al (2014) reporting that higher hope levels are correlated with better life quality; and Warber et al (2011), concluding through a spiritual intervention that hope is inversely correlated with stress and depression and associated with positive cardiovascular outcomes. Using another methodology, Gelkopf et al (2013) conducted a study in which the rehabilitation team of the Israeli Defense Forces (IDF) ran a rehabilitation program through adventures in nature.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Other benefit findings were reported in the studies of Johnson et al (2001), showing that social support for HIV-positive people is inversely related to depressive symptoms and a lack of hope; Waynor et al (2012), demonstrating that hope and symptoms are inversely related; Hawro et al (2014) reporting that higher hope levels are correlated with better life quality; and Warber et al (2011), concluding through a spiritual intervention that hope is inversely correlated with stress and depression and associated with positive cardiovascular outcomes. Using another methodology, Gelkopf et al (2013) conducted a study in which the rehabilitation team of the Israeli Defense Forces (IDF) ran a rehabilitation program through adventures in nature.…”
Section: Discussionmentioning
confidence: 77%
“…The Hope Scale (Snyder et al, 1996) was the most used instrument to evaluate hope in the studies (six out of ten). Other evaluation methods were: the Emotion Scale (Richman et al, 2005), individual qualitative interviews (Halding and Heggdal, 2012), the Beck Hopelessness Scale (Johnson et al, 2001), and the Basic Hope Inventory (Hawro et al, 2014). As for the studies that addressed both constructs, the following instruments were used: the Hope Scale Optimism–Affective valence of future perspectives scale (Schöllgen et al, 2011); the Life Orientation Test, the Gottschalk Hope Scale (Scioli et al, 1997); and the Chinese version of the Life Orientation Test and Hope Scale (Scheier and Carver, 1985; Scheier et al, 1994; Snyder et al, 1996; Scioli et al, 1997; Johnson et al, 2001; Kubzansky et al, 2001, 2002; Giltay et al, 2004; Richman et al, 2005; Hou et al, 2010; Schöllgen et al, 2011; Halding and Heggdal, 2012; Hawro et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous issue of the Archives of Dermatological Research, we were very interested in the article by Hawro et al entitled ''In psoriasis, levels of hope and quality of1 life are linked'' in which the investigators reported that the levels of hope and quality of life linked in patients with psoriasis [6]. However, we wish to make some comments on hope and quality of life in dermatological diseases especially psoriasis.…”
Section: Dear Editormentioning
confidence: 95%
“…Since the 70s, this concept has been examined in different ways, in connection to negative feelings, adaptability, and survival. Besides over time, with popularity of health psychology, the concept of hope entered a new era of theorizing (9). In hope, there is a will for realizing goals on the one hand; and on the other hand, it helps find suitable solutions in order to realize hidden goals.…”
Section: Introductionmentioning
confidence: 99%